2022
DOI: 10.1523/jneurosci.1795-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Value, Confidence, Deliberation: A Functional Partition of the Medial Prefrontal Cortex Demonstrated across Rating and Choice Tasks

Abstract: Deciding about courses of action involves minimizing costs and maximizing benefits. Decision neuroscience studies have implicated both the ventral and dorsal medial prefrontal cortex (vmPFC and dmPFC) in signaling goal value and action cost, but the precise functional role of these regions is still a matter of debate. Here, we suggest a more general functional partition that applies not only to decisions but also to judgments about goal value (expected reward) and action cost (expected effort). In this concept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
2
12
0
1
Order By: Relevance
“…Therefore, we validated the robustness of our tasks not only for assessing effort-based decision-making across physical and mental domains as shown above ( Results: Behavioral Results ), but also by confirming their ability to engage the dmPFC/dACC and aIns during such processes. This supports the documented contributions of these regions to effort valuation and decision-making 10,11,61,6771 , with our analysis distinguishing this activation from factors like subjective value perception 60,62,63 or reaction times 6466 .…”
Section: Resultssupporting
confidence: 87%
“…Therefore, we validated the robustness of our tasks not only for assessing effort-based decision-making across physical and mental domains as shown above ( Results: Behavioral Results ), but also by confirming their ability to engage the dmPFC/dACC and aIns during such processes. This supports the documented contributions of these regions to effort valuation and decision-making 10,11,61,6771 , with our analysis distinguishing this activation from factors like subjective value perception 60,62,63 or reaction times 6466 .…”
Section: Resultssupporting
confidence: 87%
“…In parallel, the role of the BVS - and, in particular, the ventromedial prefrontal cortex (vmPFC) - has been challenged by recent studies. They argue that rather than representing one’s subjective value for the object they are processing (33,34,36), the BVS could be representing slightly different variables, such as one’s goal value (5356) or one’s confidence in the rating (57,58). In the current study, control analyses found no significant evidence indicating a confound with confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from functional neuroimaging studies support the view that the orbitofrontal cortex contributes to expectation-guided decision-making by enabling us to simulate the consequences of our choices ( Kahnt ). Moreover, it was found in choice tasks that value of the items and confidence in the decision involve large parts of the medial prefrontal cortex with a specific activation for value in the ventral portion and for confidence more dorsally in the anterior portion (Claris and Pessiglione, 2022 ).…”
Section: Believing Enables Decisionsmentioning
confidence: 99%